Effectiveness of simulation in endoscopic retrograde cholangiopancreatography (ERCP) for successful bile duct cannulation: systematic review and meta-analysis - Arrieta G., Manuel (2021)
Introduction: The evidence for simulation in endoscopic retrograde cholangiopancreatography is limited. Objective: The objective of this study is to review the effectiveness of simulation in endoscopist training in endoscopic retrograde cholangiopancreatography with emphasis on the successful cannulation of the bile duct, as well as on the cannulation time and performance evaluation. Materials and methods: A systematic review was conducted in MEDLINE, EMBASE, and Web of Science, from 1970 to June 2021. Randomized clinical studies comparing endoscopic retrograde cholangiopancreatography simulated training versus traditional training were included. Results: 4 studies were included, with a total of 80 participants and 1,475 procedures. The odds ratio (OR) for successful bile duct cannulation with the use of simulation was 2.12 (95% CI, 1.60-2.81) and the mean time to cannulation was shorter compared to traditional training (p<0.001). Two studies found a better score in the global performance of endoscopists with simulated training (OR: 1.86 (95% CI 1.29-2.7)) and (OR ions: Endoscopic retrograde cholangiopancreatography simulation can improve the rformance of endoscopists in terms of time and successful bile duct cannulation.